2015
DOI: 10.1177/1040638715611170
|View full text |Cite
|
Sign up to set email alerts
|

The use of loop-mediated isothermal amplification improves Toxoplasma gondii detection in wildlife

Abstract: Abstract. Toxoplasma gondii is among the most widespread parasites worldwide. Wildlife is recognized as an important reservoir and source of infection of T. gondii. The goal of the present work was to assess the performance of loop-mediated isothermal amplification (LAMP) as a diagnostic tool for T. gondii infection in the skeletal muscle and central nervous system (CNS) of free-ranging ungulates and carnivores. Fifty-seven wild animals were tested for the presence of T. gondii DNA by polymerase chain reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…A number of studies have reported the presence of this parasite in wild rodents and members of Carnivora, Didelphimorphia, and Xenarthra (18) (19) (20) . These findings confirm the worldwide distribution of T. gondii, and highlight the wide variety of intermediate hosts that form part of the epidemiological chain responsible for transmission of this infection and the associated disease.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported the presence of this parasite in wild rodents and members of Carnivora, Didelphimorphia, and Xenarthra (18) (19) (20) . These findings confirm the worldwide distribution of T. gondii, and highlight the wide variety of intermediate hosts that form part of the epidemiological chain responsible for transmission of this infection and the associated disease.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological data for each game species included in the review are provided below. Serological and molecular studies showed a level of infection of hunted wildlife ranging from 2% to 68% [81]. Comparison of the studies should be performed carefully, considering different methodologies, lack of standardized research methods, different types, number and collection methods of tested samples and geographical and climatic differences [10].…”
Section: Epidemiology In Mammalian Game Species In the European Unionmentioning
confidence: 99%
“…Tissues samples can be examined by using immunohistochemical staining or applying molecular techniques for the detection of parasite DNA [76], by polymerase chain reaction (PCR), quantitative real-time PCR (qPCR) and loop-mediated isothermal amplification (LAMP). Quantitative real-time PCR is the most sensitive diagnostic technique; however, due to extreme simplicity and speed, LAMP provides a valuable alternative for fast and effective diagnosis in contexts where economic resources are limited and no valid alternative are available (e.g., game meat screening in rural areas) [81]. For genotyping, the PCR-RFLP method, together with the microsatellite analysis, is considered particularly useful due to its simplicity and inexpensiveness [74].…”
Section: Parasite Detection At Slaughtering and Identificationmentioning
confidence: 99%
“…Sterile water and T. gondii genomic DNA extracted from parasite cultures and identified by species-specific PCR and sequencing were used in each set of reactions as negative and positive controls, respectively. Sensitivity and specificity of the LAMP assay were assessed [21].…”
Section: Loop Mediated Isothermal Amplification (Lamp)mentioning
confidence: 99%